(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The forms of promises issued in the international community, especially from the major countries and during the presidential elections. In the recent period, since the election of Joe Biden as President of the United States of America, promises that he issued to withdraw from the decisions of the previous US administration have spread. So, what is the adaptation of international law to these promises? The matter becomes more difficult due to the absence of clear international legal rules that address the issue. Are promises in international relations only within the framework of political actions or are they such as binding legal acts? Although adherence to the promise is a moral obligation in its content, the state’s responsibility when fulfilling its promises is not limited to moral responsibility. Rather, it is considered legally responsible for compensation based on the principle of good faith according to the jurisprudence of the international judiciary.